(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The Rubaiyat is a collection of four line stanzas. Originally, it was written by Omar Khayyam, a Persian poet, but later it was translated by Edward FitzGerald into English. It is translated version of FitzGerald, established in five editions that make the Rubaiyat widely known in the world of literature, especially English literature. This study deals with the 1859 first edition. The Rubaiyat is the exposition of Khayyam’s contemplation of life and Divinity, which is highly appreciated, and of great importance in the world of literature and a stepping progress to spirituality. Concerning the contemplation of Divine existence, the poet has experienced spiritual states. These spiritual states or experiences are called Ahwal in the concept of Sufism. The Ahwal are the main concern of this study. This concept is referred to the classification of Ahwal given by Qushayri (1966). There are six forms of Ahwal expressed by Omar Khayyam in the Rubaiyat. They are Wajd `Ecstacy’, Dzawq `Taste’, Fana `Exctincion’, Baqa `Permanency’, `Ishq `Divine Love’, and Sukr’ `Intoxication’. Then, it is found that the six spiritual states, Ahwal, are undergone by Omar khayam and they are replected through his Rubaiyat.